Impact of SARS-CoV-2 infection on clinical outcomes of in vitro fertilization treatments: a systematic review and meta-analysis - Xue, Yamei; Xiong, Yuping; Cheng, Xiaohong; Li, Kun (Frontiers in Endocrinology, 2023)
The influence of SARS-CoV-2 infection on clinical outcomes in patients undergoing in vitro fertilization has been uncertain. Therefore, this systematic review and meta-analysis aimed to evaluate the impact of past SARS-CoV-2 infection on IVF outcomes. A comprehensive search of PubMed, EMBASE, and Cochrane Library databases was conducted from December 2019 to January 2023. Included studies comparing IVF outcomes between patients with prior SARS-CoV-2 infection and controls without previous infection were analyzed. Study quality was assessed using the Newcastle-Ottawa Quality Assessment Scale. Sensitivity analysis, publication bias, and heterogeneity were also examined. The review protocol was registered with PROSPERO (CRD42023392007). A total of eight studies, involving 317 patients with past SARS-CoV-2 infection and 904 controls, met the inclusion criteria. The meta-analysis revealed no significant differences between the infection group and controls in terms of clinical pregnancy rate (OR 0.97, 95% CI 0.73-1.29; P = 0.82), implantation rate (OR 0.99, 95% CI 0.67-1.46; P = 0.96), or miscarriage rate (OR 0.64, 95% CI 0.15-2.65; P = 0.53). Subgroup analyses based on transfer type demonstrated comparable clinical pregnancy rates between the two groups in both fresh embryo transfer (OR 0.97, 95% CI 0.69-1.36; P = 0.86) and frozen embryo transfer (OR 0.96, 95% CI 0.38-2.44; P = 0.94). In conclusion, this meta-analysis suggests that previous SARS-CoV-2 infection does not have a detrimental impact on clinical outcomes in IVF patients. These findings provide valuable insights into assessing the influence of prior SARS-CoV-2 infection on successful pregnancy outcomes in IVF treatment.